ANTIBIOTICS FOR TREATMENT OF ACUTE APPENDICITIS : A SYSTEMATIC REVIEW - Rhomadani Putra, Windy; Rochmahyanti, Atika (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2024)
Background: Appendicitis is one of the most common causes of acute abdominal discomfort in adults and children, with a lifetime risk of 8.6 in males and 6.7 in females. Methods: By comparing itself to the standards set by the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) 2020, this study was able to show that it met all of the requirements. So, the experts were able to make sure that the study was as up-to-date as it was possible to be. For this search approach, publications that came out between 2014 and 2023 were taken into account. Several different online reference sources, like Pubmed and SagePub, were used to do this. It was decided not to take into account review pieces, works that had already been published, or works that were only half done. Result: In the PubMed database, the results of our search brought up 259 articles, whereas the results of our search on SagePub brought up 148 articles. The results of the search conducted for the last year of 2014 yielded a total 15 articles for PubMed and 11 articles for SagePub. In the end, we compiled a total of  6 papers, 4 of which came from PubMed and 2 of which came from SagePub. We included six research that met the criteria. Conclusion: In summary, when selecting antimicrobial medications to treat acute appendicitis, patients who are especially worried about recurrence of appendicitis should use caution. Patients who failed antibiotic treatment first and underwent surgery later could not possibly result in a higher risk of postoperative complications and the acute appendicitis does not develop to complicated appendicitis in this course, which made antibiotic treatment appealing for patients with acuteacute appendicitis who do not want surgery without having to worry about complications or complicating the original illness.